Fasting hyperglycemia, drugs and medicinal plants in a clinical laboratory in Oaxaca, Mexico - Ramírez Velázquez, Fernando A.; Almenares López, Damianys (Horizonte Sanitario, 2022)
Objetive: To determinate the prevalence of fasting hyperglycemia and the use ofdrugs and medicinal plants in patients trated at the HECA LAB clinical analysislaboratory in Ciudad Ixtepec, Oaxaca.Materials and Methods: A descriptive, cross-sectional study was carried outduring the fourth quarter of 2021. A non-probabilistic sampling was carriedout, for convenience, incluiding a total of 205 patients. Data collection wascarried out by applying a structured questionnaire containing sociodemographicinformation such as age and sex. Patients with hyperglycemia were questionedabout the consumption of medicines and medicinal plants. Glucose levels weredetermined using the Mindray semi-automatic clinical chemistry analyzer,model BA-88A. A glucose value greater than or equal to 126 mg/dl accordingto the WHO criteria was considered diabetic. Prevalence was calculated byformula, according to Aschengrau & Seage.Results: Of the 205 patients, 29% had diabetes. 8% were classified as prediabeticwith a predominance of females. The most frequent age range was 54-65 yearswith 32%. 82% reported taking pharmacological treatment and 63% of thosesurveyed reported consuming medicinal plantas for the treatment of diabetes.Conclusions: The prevalence of diabetes in the studied patients was 29%. Oralmonotherapy with metformin was the most frequent treatment, followed bythe use of subcutaneous insulin. Eleven medicinal plants were referred, beingmoringa (Moringa oleifera), the most used. 18% did not receive pharmacologicaltreatment. For this reason, it is necessary to establish timely health educationinterventions on lifestyle changes and adherence to pharmacological treatment ofpatients with diabetes mellitus; to achieve adequate management of the diseaseand avoid complications.Keywords: Prevalence; Diabetes; Drug therapy; Medicinal plants; Epidemiology